Luuanda e os filhos da Pátria: leituras em movimento - Camargo, Patrícia (2010)
This work considers a reflection on the paper of the representation of the utopia in two angolan ficcionais workmanships, searching to investigate as this utopian element in them a component functions as that makes possible arising of the critical conscience. One is overcome as specific object of study Luuanda, of the José Luandino Vieira and Filhos da pátria, of the João Melo. It is intended to show the way as literary speech takes the reader to a reflection on the importance of the utopia as a endurance form.